Underworld : awakening [videorecording (Blu-Ray)] - Mårlind, Måns; Stein, Björn; Beckinsale, Kate; Rea, Stephen; Ealy, Michael (Sony Pictures Home Entertainment, 2012)
Vampire Selene leads the battle against humans after they discover the existence of the Vampire and Lycan clans and try to eradicate them.